Contribution of the University Educational and Scientific Ecosystem in the Formation of a Regional Innovation System - Yuri PREOBRAZHENSKIY (Communications of International Proceedings, 2020)
Currently, universities largely determine the effectiveness of the formation of a regional innovation system and become a significant driver of innovative growth. The university is increasingly acting as an integrator, on the basis of which new knowledge is created and commercialized. Such integration can be carried out by understanding the principles of interaction between different actors and the principles of manifestation of a synergistic effect in the course of it. The application of the ecosystem model makes it possible to build an integral, consistent description of the processes of co-development and mutual enrichment of knowledge between the participants in the system. The nature of the dissemination of knowledge and its importance for the manifestation of externalities that allow the use of knowledge by all participants in the ecosystem are discussed. The balance of the educational and scientific ecosystems in the regions of Russia is estimated. Further research is associated with an empirical analysis of the interaction between the participants in the educational and innovation processes, the search for practices of optimal interaction between them on the example of specific regions.
Keywords: University Ecosystem; Knowledge Spillover; Regional Innovation Ecosystem